Communication Management of the Organic Vanilla Business in Gadut, Agam Regency - Oktavia, Yenny; Nofialdi; Ifdal; Ami Sukma Utami; Nabila Khairani Wardah; Oryza Vicasindi (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
Vanilla is an Indonesian export commodity with a high selling value and great potential for development in Indonesia. This study aims to analyze the stages in the communication management of the organic vanilla business in Tilatang Kamang District, Agam Regency, starting from the communication planning stage, goal setting, and communication strategy formulation. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with stakeholders, field observations, and a review of relevant documents. The research findings show that although there have been several efforts to improve communication management in the organic vanilla business in Tilatang Kamang District, there are still some constraints such as the lack of coordination and synchronization among stakeholders, the limited understanding of farmers about the organic vanilla production standards required by the market, as well as the suboptimal communication network among organic vanilla business actors in the region.